An Exploratory Study on the Potential of Implementing Building Information Modelling (BIM) in Malaysian Construction Industry: Lesson Learnt from Singapore and Hong Kong Construction Industry - Zahrizan, Zakaria; Nasly, Mohamed Ali; Amanda, Marshall Ponting; Ahmad Tarmizi, Haron; Zuhairi, Abd Hamid (Penerbit UMP, 2012)
For a decade, construction industry can be considered as a fragmented industry because of lacking of sharing information through its life cycle and with other parties. Information Technology (IT) can be a tool for integrating and collaborating among parties in the construction projects, and Building Information Modelling (BIM) is one of the platforms that can be used to promote the collaboration between parties in the construction projects. Basically, BIM will act like a respiratory system with full of information to share with for construction projects. Even though there are lots of benefits can be gained by utilisation of BIM, it is a difficult task to convince the construction companies to embrace and implementing it due to some reasons. Since there is a sort of understanding of BIM by the construction companies in Malaysia. This paper is intended to review the strategy and action plan from Singapore and Hong Kong in adopting and implement BIM, which could be used in supporting the implementation of BIM in Malaysian Construction Industry. Therefore, this paper reviews the strategy and action plan from Singapore and Hong Kong in adopting and implement BIM, which could be used in supporting the implementation of BIM in Malaysian Construction Industry. Malaysia could learn from these countries because they can be classified as a new comer in implementing BIM compared to other's countries such as the United States of America, United Kingdom, Finland, Denmark, Australia and Norway, which are more advanced in implementing BIM.